Carbon from waste source: An eco-friendly way for strengthening polymer composites. (1st January 2018) - Khan, Aamer; Jagdale, Pravin; Rovere, Massimo; Nogués, Marc; Rosso, Carlo; Tagliaferro, Alberto
Abstract: Carbon nano materials (CNMs) from waste polyethylene bags were synthesized in two different morphologies namely carbon nano beads (P1) and a mix of carbon nano tubes and carbon nano beads (P2) using chemical vapour deposition (CVD) technique. Morphology of the CNMs were studied through field emission scanning electron microscope (FESEM) and the purity through thermogravimetric analysis (TGA) and Raman spectroscopy. Epoxy composites were produced using these CNMs as filler in 1% and 3% by weight. Mechanical properties and tribological properties were compared with the composites of commercial Multi Walled Carbon Nano Tubes (MWCNT). It is observed that the in house generated CNMs composites show overall better mechanical and tribology properties compared to the blank epoxy and the commercial MWCNTs based composites. Morphology of the composites was analysed through FESEM to study the interaction of the filler with the matrix that lead to improved performances. Graphical abstract: